Demolition of Existing Buildings in Urban Renewal Projects: A Decision Support System in the China Context - Kexi Xu (Sustainability, 2019)
Much of the rapid urbanization of China’s cities has occurred at the expense of the existing urban fabric. Across the nation, whole city blocks have been replaced with new structures, requiring large numbers of buildings to be demolished while still serviceable. This curtailed lifespan of existing buildings not only comes with an economic cost, but results in loss of urban culture, wastes resources, degrades the environment, exacerbates pollution, and inflames social conflict and instability. For the purpose of evaluating the merits of building demolition, this study develops a decision support system (DSS) for building demolition in the China context from the perspective of sustainable urban renewal. The indicators of this system cover economic, social, environmental, and institutional aspects of sustainable development. Meanwhile, both the individual characteristics of buildings and the external or extrinsic indicators at the neighborhood, local, or city level are taken into account. Based on exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), 24 critical indicators containing qualitative and quantitative factors are identified. These indicators are classified into six parameters: (1) service performance; (2) economic impact; (3) social identity; (4) local development; (5) building location; and (6) building safety. Empirical results reveal considerations of local development to be of greatest significance with the value of standardized factor loading standing at 0.911, followed by service performance (loading = 0.870) and building location (loading = 0.863), with social identity (loading = 0.236) ranking substantially lower. The findings contribute to the practice of urban renewal and, in particular, provide practical guidance to the building demolition decision-making process.